Шепот, робкое дыханье...: [стихи] / Афанасий Фет - Фет Афанасий Афанасьевич (Золотая серия поэзии, 2017)
Экземпляры: ф.6 (20190726) / Инвентарный номер: 2852zzz / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Ф 45 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)1-4